On Some Fixed Point Results for H+-Type Contraction Mappings in Metric Spaces. (6th July 2015) - Pathak, Hemant Kumar; Rodríguez-López, Rosana
Abstract : We prove some fixed point theorems forH + -type multivalued contractive mappings in the setting of Banach spaces and metric spaces. The results provided allow recovering different well-known results.